Generational diversity and reporting of unethical practices : a cross-country analysis - Lopes, Manuel Nuno de Azevedo (2024)
This thesis delves into the complexities of ethical decision-making among employees of different generations across 13 countries, using data from the UK Institute of Business Ethics' Ethics at Work 2021 employee survey. Focusing on the awareness and response behaviors towards ethical misconduct within workplaces, the study challenges traditional assumptions regarding age-related superiority in ethical reasoning. Drawing upon an extensive body of literature, the findings suggest that younger generations may indeed possess stronger ethical values, indicative of societal shifts prioritizing ethics in professional settings. Contrary to conventional generational theories, which posit older employees' superior ethical judgment, this study proposes a contradictory hypothesis: that younger employees may surpass their older counterparts in ethical awareness and proactive behavior. Through an analysis of survey data and a discussion of nuanced dynamics of employee voice across different generations and countries, the study sheds light on factors influencing speak up behavior, consequences of speaking up, and the role of cultural diversity. This study shows the intricate interplay between generational differences, ethical awareness, and response behaviors. By recognizing and addressing these dynamics, organizations can strive towards fostering more inclusive and ethically sound work environments conducive to employee well-being and organizational success.